Mixed volatility in a single device: memristive non-volatile and threshold switching in SmNiO3/BaTiO3 devices - Hamming-Green, Ruben; Van den Broek, Marcel; Bégon-Lours, Laura; Noheda, Beatriz (Frontiers in Materials, 2024)
Analog neuromorphic circuits use a range of volatile and non-volatile memristive effects to mimic the functionalities of neurons and synapses. Creating devices with combined effects is important for reducing the footprint and power consumption of neuromorphic circuits. This work presents an epitaxial SmNiO3/BaTiO3 electrical device that displays non-volatile memristive switching to either allow or block access to a volatile threshold switching regime. This behavior arises from coupling the BaTiO3 ferroelectric polarization to SmNiO3 metal–insulator transition; the polarization in the BaTiO3 layer that is in contact with the SmNiO3 layer modifies the device resistance continuously in a controllable, non-volatile manner. Additionally, the polarization state varies the threshold voltage at which the Joule-heating-driven insulator-to-metal phase transition occurs in the nickelate, which results in a negative differential resistance curve and produces a sharp, volatile threshold switch. Reliable current oscillations with stable frequencies, large amplitude, and a relatively low driving voltage are demonstrated when the device is placed in a Pearson–Anson-like circuit.